Accurate and Objective Lecturer Appraisal System: Implementation of the LOPCOW Method - Sumanto, Sumanto; Radiyah, Ummu; Supriyatna, Adi; Pujiastuti, Lise; Yani, Ahmad; Marita, Lita Sari (Ilmu Komputer, FMIPA, Universitas Pakuan, 2024)
This research proposes the use of the Logarithmic Precursor Chain-Driven Objective Weighting (LOPCOW) method to evaluate the best lecturers in universities. The LOPCOW method ensures that the assessment covers all aspects of lecturer quality and performance, including education, research, community services, discipline, commitment, cooperation skills, and innovation. The evaluation of lecturers using the scores and ratings provided showed that CDE lecturers were the best, with the highest score of 0.715. CDE lecturers showed high consistency in all aspects assessed, especially in education, research, and community service. This was followed by MNO lecturers (0.676), STU lecturers (0.668), XYZ lecturers (0.637), and AFI lecturers (0.627). In conclusion, highly ranked lecturers showed strong dedication to the Tridharma of higher education, with consistent performance and a positive impact on the academic community and the general public. Future research should focus on developing strategies to improve lecturers' teaching quality by applying new educational technologies and evaluating their impact on student learning.